Numerical Simulation of Flexible Riser under Torsion - Liu, M.S.; Liu, X.W.; Li, J.Y.; Ju, J.S. (Проблемы прочности, 2017)
The 10-layer unbonded flexible riser is modeled with parametric modeling technology in FEM and the model is imported into ABAQUS to simulate the riser’s mechanical behavior under the load condition: torsion. FEM model considering material nonlinearity and nonlinear boundary conditions (the interaction between layers) has been set to simulate the structure of riser exactly. Based on the detailed finite element model, the influence of friction coefficient on the calculation results of the riser under torsion force is studied. The computation demonstrates that there is great difference between layers and the tension armor (consisted of steel strips) is the main bearing layer. Besides, the friction coefficient has great influence on the result of the calculation.